Current applications of adipose-derived mesenchymal stem cells in bone repair and regeneration: A review of cell experiments, animal models, and clinical trials - Zhang, Zhengyue; Yang, Xiao; Cao, Xiankun; Qin, An; Zhao, Jie (Frontiers in Bioengineering and Biotechnology, 2022)
In the field of Orthopaedics, bone defects caused by severe trauma, infection, tumor resection and skeletal abnormalities are very common. However, due to the lengthy and painful process of related surgery, people intend to shorten recovery period and reduce the risk of rejection, new attention paid to bone regeneration with mesenchymal stromal cells, one of which is the adipose-derived mesenchymal stem cells (ASCs) from adipose tissue. After continuous subculture and cryopreservation, ASCs still have the potential of multidirectional differentiation. They can be implanted in human body to promote bone repair after induction in vitro, solve the problems of scarce sources and large damage, and is expected to be used in the treatment of bone defects and non-union fractures. However, the diversity of its differentiation lineage and the lack of bone formation potential limit its current applications in bone disease. Here, we concluded the current applications of ASC in bone repair especially with the combination and use of physical and biological methods. ASC alone has been proved to contribute to the repair of bone damage in vivo and in vitro. Attaching to bone scaffolds or adding bioactive molecules can enhance the formation of bone matrix. Moreover, we further evaluated the efficiency of ASC committed differentiation into bone in conditions of cell experiments, animal models, clinical trials. The results show that ASCs in combination with synthetic bone graft and biomaterials may affect the regeneration, augmentation and vascularization of bone defects on bone healing. The specific conclusions of different materials applied with ASC may vary. It has been confirmed to benefit osteogenesis by regulating osteogenic signaling pathway and gene transduction. Exosomes secreted by ASCs also play an important role in osteogenesis. This review will illustrate the understandings of scientists and clinicians of the enormous promise of ASCs current applications and future development in bone repair and regeneration, and provide incentive for superior employment of such strategies.